Aspectos moleculares associados à cardiomiopatia chagásica e à reativação da infecção em pacientes cardiopatas transplantados. - Priscilla Almeida da Costa (2019)
About 20 to 30 percent of people infected with Trypanosoma cruzi develop Chagas heart disease, showing cardiac complications that can lead to heart failure or sudden death and establish chronic chagasic cardiomyopathy in its most advanced stage, being the third leading indication for heart transplant in Brazil. However, immunosuppression – necessary for the control of transplant rejection – is a complicating aspect for chagasic patients, since it increases the chance of reactivation of the infection. The differential diagnosis between implant rejection and reactivation of Chagas disease has been considered difficult, preventing thus the correct treatment. In addition, the reason why some chagasic patients undergoing heart transplantation have reactivation of the disease is still unknown. It is estimated that these factors are related to both the genetic variability of the parasite and the host. In this sense, in the present work we investigated (i) the possibility of using methodologies based on PCRs directed to nuclear (rDNA 24Sα) and mitochondrial (kDNA) markers for early diagnosis of the presence of T. cruzi in transplanted chagasic patients; (ii) the occurrence of T. cruzi subpopulations most associated with reactivation of infection, using a triple assay for determination of DTUs (COII gene analysis, miniexon intergenic spacer and 24Sα rDNA) and microsatellite polymorphisms (TcCAA10, TcTAT20 , TcAAAT6, TcGAG10, TcATT14, TcTAT15); and (iii) the existence of association of genetic polymorphisms of the patients (genes encoding IL-1α, IL-6, IL-10 and IL-17) with chagasic reactivation and/or rejection of post-transplant. For this, 991 endomyocardial biopsies (EMB), derived from the cardiac transplantation follow-up of 98 chagasic patients, were analyzed in addition to 14 skin biopsies, and three obtained from the central nervous system (CNS) – the latter in cases of cutaneous or neurological reactivation. The presence of T. cruzi DNA was detected in 205 EMB from 70 patients, eight skin biopsies and in three of the CNS biopsies. During the 10 years of follow-up, from the 70 patients who had some PCR positive for the DNA of the parasite, approximately 73% had some clinical reactivation episode of Chagas disease. When compared to other diagnostic techniques (blood smear, histopathological analysis of EMB, conventional or with immunohistochemistry), we observed that the PCR technique proposed in this study revealed superior sensitivity with good specificity and was able to anticipate reactivation of Chagas disease between 1.5 and 36 months (median 6, mean 9.1 months). Thus, the adoption of this methodology, besides contributing to the early diagnosis of the reactivation of the infection, presents potential to assist the doctors in the treatment decisions. Regarding the genetic factors of the parasite possibly associated with reactivation, the genotyping of 184/216 positive samples for the presence of T. cruzi demonstrated that most patients had reactivation by TcII, reinforcing the fact that this is the main DTU associated with the form cardiac disease and the different clinical forms of post-transplant chagasic reactivation, at least in the geographic region studied. However, a case of initial TcI infection with TcVI reactivation was observed, indicating that parasite strains may vary during reactivation episodes, and that other DTUs may also be associated with Chagas heart disease in southeastern Brazil. Interestingly, the comparison between samples obtained from explanted hearts and transplanted hearts showed, in all analyzed cases, that the population of the predominant parasite in the reactivation episodes was different from that detected in the heart of the patient at the time of transplantation, even among those patients who maintained the same DTU during reactivation. In relation to host genetic polymorphisms, we obtained intriguing results for the genes encoding IL-10 and IL-17. Regarding the IL10 polymorphism (-1082 G/A), the presence of the G allele associated with the increased production of the anti-inflammatory cytokine IL-10, in the donor and recipient was correlated with greater rejection of the cardiac graft. For the IL17A polymorphism (-197 vi A/G), the presence of the A allele associated with increased production of the proinflammatory cytokine IL-17, in the donor was correlated with a greater susceptibility to early reactivation of Chagas disease in transplant patients. In parallel with these studies, our ultimate goal was to investigate with an experimental Chagas disease approach, contributions of parasite and host factors in differential tissue tropism, more specifically to the placenta, and congenital transmission. For this, we investigated the effects in the placental environment of the infection of C57Bl/6J mice with two strains of T. cruzi of different DTUs, VD (TcVI) and K98 (TcI), analyzing the gene expression and parasite persistence in this tissue. There was a greater development of an immune response against VD infection, possibly due to the stronger placental tropism displayed for this strain, reiterating the idea that DTU VI is associated with an increased risk for vertical transmission of Chagas disease.